(3TQM fgL GdHdGZIs - (3YR GdOjf YHO GdMejO Hf GHi GdMOjO GdedGjfi eYJRdis; (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd GdCUd hef cdGe dg Ydjg GdSdGe (B( (3CjgG GdfGS OGQ eMGQ hGdGNQI OGQ bQGQ Edi GdTQM s
(3BNQgG (B:s
(3hdgPG GdeYfi Sei GHh SajGf Hf MQH BNQ GdLRA GdMGOi YTQ hgh BNQ GdLRA GdKGdK s
(3ChQGb fe L(B3s
(3Ydjg hbas
(3GdeNWhW YHGQI Yf GhQGb ef HOGjI GdcJGH hfgGjJg abWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1991s
Keywords: (3GdHdGZIs